Upper Position and Distraction Model Of Bobath Ball Towards Reduction In Immunization Pain Level - Waladani, Barkah; Utami, Wuri; Ernawati, Ernawati (STRADA : Jurnal Ilmiah Kesehatan, 2020)
This study used an experimental design, namely Quasi-experimental post-test only with non-equivalent control group design. The samples in this study were infants aged 7-9months in the last 6 months from October 2019-March 2020 who met the criteria. Pain was measured using the MBPS (Modifield Behavior Pain Scale) instrument. The results obtained a pre average pain of 3.07. Wilcoxon test obtained p 0.001, where giving a bobath ball in an upright position can reduce pain in infants during immunization. Respondents’ pain response was lower after giving the bobath ball, which was measured using MBPS. The MBPS instrument consists of 3 indicators, namely facial expressions, crying expressions and movement expressions. Patients showed a mean reduction in pain with a post score of 2.23. There were differences in the pain response in children before and after being given the bobath ball upright position